2011
DOI: 10.1038/npp.2011.148
|View full text |Cite
|
Sign up to set email alerts
|

Laminin-β1 Impairs Spatial Learning through Inhibition of ERK/MAPK and SGK1 Signaling

Abstract: Laminin is a major structural element of the basal lamina consisting of an α-chain, a β-chain, and a γ-chain arranged in a cross-like structure, with their C-terminal inter-coiled. Laminin is abundantly expressed in the hippocampus of mature brain and is implicated in several psychiatric disorders, but its possible role involved in learning and memory function is not known. This issue was examined here. Our results revealed that water maze training significantly decreased laminin-β1 (LB1) expression in the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…One lab has produced mechanistic evidence for a role for laminin β1 in synaptic plasticity. Molecular mechanisms of learning and memory were investigated by gene manipulation in vivo in rat hippocampus in combination with water maze testing ( Yang et al, 2011 ). Maze learning decreased laminin β1, and conversely laminin β1 overexpression impaired maze performance.…”
Section: Discussionmentioning
confidence: 99%
“…One lab has produced mechanistic evidence for a role for laminin β1 in synaptic plasticity. Molecular mechanisms of learning and memory were investigated by gene manipulation in vivo in rat hippocampus in combination with water maze testing ( Yang et al, 2011 ). Maze learning decreased laminin β1, and conversely laminin β1 overexpression impaired maze performance.…”
Section: Discussionmentioning
confidence: 99%
“…Laminins are canonical ECM integrin ligands and a subset of laminin chains is specific to integrin α3β1 (Belkin and Stepp, 2000; Nishiuchi et al, 2006). Several laminin subunit chains are expressed in the hippocampus (Chen et al, 2003; Indyk et al, 2003; Egles et al, 2007) where they influence synapse density and ultrastructure (Egles et al, 2007) and spatial learning in mice (Yang et al, 2011). Although Reelin conventionally signals through Dab1 (Dulabon et al, 2000; Niu et al, 2008) and Netrins are known to signal via Frazzled/DCC (Stanco et al, 2009; Qu et al, 2012), both proteins can also bind integrinα3β1 and thus are also candidates for initiating stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest a neuroprotective role of laminins in neurodegeneration. In sharp contrast to these reports, one study reported that laminin‐β1 impaired spatial learning through inhibition of MAPK/ERK and serum and glucocorticoid‐regulated kinase 1 (SGK1) signalling (Yang et al ., ), suggesting a detrimental role of laminin‐β1 in neurodegeneration. This discrepancy may be explained by different experimental models and/or different functions of distinct laminin isoforms.…”
Section: Functions Of Laminins and Their Receptorsmentioning
confidence: 97%